PENGENDALIAN SOSIAL DALAM MENGATASI PERILAKU MEMBOLOS DI SMA SANTUN UNTAN PONTIANAK - Made Semi Naresswari; Yohanes Bahari; Imran Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractThe objective of this research is to discover social control of the school in order to solve truant in SMA Santun Untan Pontianak. The approach that used in this research is a qualitative approach with descriptive method. The techniques that used in collecting data are observation, interview, and documentation study. The analysis in this research is presented in qualitative descriptive with 12 informants, which consist of 1 vice head master of the student section, 1 guidance and counseling teacher, 2 Homeroom teachers, and 8 truant students. The result of this research showed that the social control in SMA Santun Untan Pontianak is contents of preventive control through socialization and advice to the students. Meanwhile, the repressive control is punishment, calling parents, statement letter and suspension. The result of this social control still cannot change the students behaviour significantly by calling the parents and also by giving statement letter.Keywords: Social Control, Truant, Student